EFFECTIVENESS OF DIFFERENTIAL TEACHING METHODS AND MIXED LEVEL CLASSES - Xaydarova Shoira,; Berdimurodova Dildora Qaxramon qizi, (TADQIQOTLAR, 2026)
Annotation: This article examines the effectiveness  of differentiated teaching methods  in  mixed  level  classrooms,where  students  demonstrate  varying abilities,learning styles,and academic needs.The study highlights how differentiated instruction  through  flexible  grouping,  varieted  task,adaptive  materials,and  learner-centered  strategies  —can  enhance  student  engagement,  motivation,  and  academic achievement. Special attention is given to the role of teachers in identifying individual differences  and  designing  inclusive  learning  environments  that  support  both  high-achieving and struggling learners. The findings suggest that differentiated teaching methods  contribute  to  more  equitable  learning  outcomes,  improved  classroom interaction, and the development of learners’ autonomy. The article concludes that, despite certain challenges such as increased planning time and classroom management demands,  differentiated  instruction  remains  an  effective  approach  for  addressing diversity in mixed-level classes.